Hypertension Awareness, Treatment, and Control in Adults With CKD: Results From the Chronic Renal Insufficiency Cohort (CRIC) Study - Muntner, Paul (2009)
BACKGROUND: A low rate of blood pressure control has been reported among patients with chronic kidney disease (CKD). These data were derived from population-based samples with a low rate of CKD awareness. STUDY DESIGN: Cross-sectional SETTING & PARTICIPANTS: Data from the baseline visit of the Chronic Renal Insufficiency Cohort (CRIC) study (n=3612) were analyzed. Participants with an estimated glomerular filtration rate of 20 to 70 ml/min/1.73m(2) were identified from physician offices and review of laboratory databases. OUTCOMES: Prevalence and awareness of hypertension, treatment patterns, control rates and factors associated with hypertension control. MEASUREMENTS: Following a standardized protocol, blood pressure was measured three times by trained staff and hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg and/or self-reported antihypertensive medication use. Patients’ awareness and treatment of hypertension were defined using self-report and two levels of hypertension control were evaluated: systolic/diastolic blood pressure <140/90 mmHg and <130/80 mmHg. RESULTS: The prevalence of hypertension was 85.7%, and 98.9% of CRIC participants were aware of this diagnosis, 98.3% were treated with medications while 67.1% and 46.1% had their hypertension controlled to <140/90 mmHg and <130/80 mmHg, respectively. Of CRIC participants with hypertension, 15%, 25%, 26% and 32% were taking one, two, three and four or more antihypertensive medications, respectively. After multivariable adjustment, older patients, blacks, those with higher urinary albumin excretion were less likely while participants taking ACE-inhibitors and angiotensin receptor blockers were more likely to have controlled their hypertension to <140/90 mmHg and <130/80 mmHg. LIMITATIONS: Data were derived from a single study visit. CONCLUSIONS: Despite almost universal hypertension awareness and treatment in this cohort of patients with CKD, rates of hypertension control were sub-optimal.